Transcriptome assembly and annotation of Pyrrosia piloselloides: a potential pipeline reference for future fern transcriptome assembly and analysis - Colendrino, Esteban Ira Patricia (Nanyang Technological University, 2022)
As ferns are such a diverse clade and hold an important evolutionary role as the sister group of angiosperms, the generation and analysis of their genomes would benefit the plant research community. The use of transcriptomic approaches has made it possible for greater insights into the fern genome. However, most transcriptomes were usually generated from one or two organs and thus would not be a good representation of the fern’s whole transcriptome. In this project, a multi organ-based assembly and annotation pipeline, with the aim of generating a more comprehensive fern transcriptome, using Pyrossia piloselloides as a model plant, was proposed. This pipeline can then be referenced for future fern transcriptome assembly, gene expression atlas generation and organ-specific gene identification. In addition, two different multi-organ De Novo assembly pipelines were compared and analzyed. Pipeline two which generated a higher quality transcriptome was concluded as the desired assembly method for our pipeline. The created Pyrossia piloselloides transcriptome had 130421 transcripts which recovered 1348 conserved embryophyta genes and 36443 transcripts identified as organ-specific. Even though there is still a need for optimization and further evaluation of the pipeline, it is a favourable step towards the generation of complete fern transcriptomes.